Emergence of an Adaptive Leadership Model from the Collective Practices of Public Secondary School Principals during COVID-19 Education Crisis - Famero, Andrew (Romblon State University Research Journal, 2024)
This qualitative study generates an adaptive leadership model based on the emerging school leadership practices among public secondary school principals during COVID-19 pandemic. Utilizing Colaizzi’s method (1978) of thematic analysis, this study investigated the lived experiences of principals in managing their respective schools at the peak of Covid-19 pandemic. Using an instrument based on the leadership domains mandated in the Philippine Professional Standards for School Heads (PPSSH), data were gathered through a semi-structured in-depth individual interview and focus group discussions (FGD) from nine school principals in Tablas Island, province of Romblon. Results showed that nine themes emerged as adaptive leadership practices namely: leadership style, stakeholder involvement, monitoring and evaluation, resource management, data management, health protocols, curriculum review and contextualization, quality teaching and assessment, and teacher support. Moreover, during Covid-19 pandemic, the secondary principals did not deviate from the PPSSH legally mandated leadership domains but in congruence with these, they strategized and devised ways utilizing the nine adaptive leadership practices in successfully running their respective schools during the education crisis.